Differential diagnosis of acute myocardial injury: a case report and discussion - S. A. Boldueva; D. S. Evdokimov; L. S. Evdokimova; A. D. Khomulo; M. V. Rozhdestvenskaya (Российский кардиологический журнал, 2020)
The article describes a case report of acute myocardial injury developed against the background of systemic inflammatory response in a patient with chronic tonsillitis exacerbation, who had no signs of coronary artery atherosclerosis and pathological changes according to cardiac magnetic resonance imaging. The differential diagnosis and discussion of the problem of acute non-ischemic myocardial injury are presented.